Penerapan Prinsip-Prinsip Good Governance Dalam Mewujudkan Kualitas Pelayanan Publik Pada Dinas Perdagangan Kabupaten Kediri - Erfan Hidayat; Teguh Pramono; Imam Fachruddin; Fendy Artha Prissando (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2023)
This research takes a case study at the Kediri Regency Trade Office in applying the principles of Good Governance in realizing the quality of public services. This type of research is descriptive research using a qualitative approach. The data collection technique used interviews with selected informants, namely apparatus at the Market UPTD, and the Kediri District Trade Office. Data analysis uses an interactive model of four stages, namely data collection, data condensation, data presentation, and drawing conclusions. The results of this study state that the application of the principles of Good Governance at the Kediri Regency Trade Service is quite good but has several notes. The record is in terms of transparency and participation. Transparency must be further strengthened by commitment between stakeholders in its implementation. Meanwhile, participation can be said to be not very participatory, because it has not involved the community when formulating policies. Supporting factors consist of 3 (three) things, namely the role and support of the leadership, a collaboration between governments, and direct supervision from law enforcement officials. While the inhibiting factors consist of 3 (three) things, namely the head of the service which is not yet definitive, limited human resources, and reports from NGOs.